Survival and Sustainability: Indigenous Knowledge and Skills of the Musahar Community in Nepal - Thakur, Radheshyam (Journal of Indigenous Knowledge and Practice, 2025)
The Musahar community, one of the most underserved indigenous groups in Nepal, possesses a rich knowledge and skill base that has enabled them to thrive and sustain themselves. This research paper explores the traditional livelihoods, local knowledge systems, and skills of the Musahar community. It highlights their deep understanding of the planet’s ecosystems, their sustainable resource management practices, and their resilience in the face of environmental disasters and climate change. The paper examines the relationship between the Musahar community and the shifts brought about by modern living, including the decline of knowledge from older generations, challenges in accessing formal education, and government policies that hinder traditional employment opportunities. The findings suggest that integrating the community’s native expertise into schools, securing land and property rights, and providing skill training programs can promote sustainable development. The research presents recommendations for enhancing the Musahars’ living standards while preserving their cultural practices.